Paratransit shaping the flexible transport future - Mulley, Corinne; Nelson, John D., active 2016. (Bingley, U.K. : Emerald, 2016)
The 1970's and 1980's witnessed both substantial conceptual and practical interest in paratransit across Europe and North America, as well as widespread implementation of paratransit services and strategies. Subsequently, the trajectory of paratransit (also often referred to as flexible transport systems) has waned, to the point where it is frequently relegated to a very narrow niche (often related to special needs) in the spectrum of collective transport services. More recently, technological advances have made feasible new and / or improved approaches for organizing and delivering local passenger transportation. With practice, policy and research in paratransit now being impacted by these developments, a new set of possibilities is emerging. Some practitioners have forged ahead over the past decade and implemented services and organizational models that show the way forward for what is possible, sometimes without the benefit of the most advanced available technologies. This book draws on a selection of papers presented at the International Paratransit Conference in Monterey in October 2014 to capture these exciting developments.
Introduction / Corinne Mulley, John Nelson -- Paratransit: the need for a regulatory revolution in the light of institutional inertia / Marcus Enoch, Stephen Potter -- The paratransit brokerage model: removing barriers and containing costs / Alaina Macia<U+0301> -- Development and status for large-scale demand responsive transport / Yngve Westerlund -- German experiences with volunteer-based paratransit and public transport / Martin Schiefelbusch -- A visualisation tool for planning passenger transport services in rural and low-demand settings / C. David Emele, Steve Wright, Richard Mounce, Cheng Zeng, John Nelson -- Paratransit cost-allocation model adjustments to promote agency ridesharing and vehicle timesharing / Steve Yaffe -- Decision making in flexible transport: the importance and application of the "golden rule<U+201d> / Corinne Mulley, Geoffrey Clifton -- International perspectives on paratransit policies and approaches to deliver accessible transportation / Eliane Wilson -- From the concept of flexible mobility services to the "shared mobility services agency<U+201d> / Giorgio Ambrosino, John Nelson, Marco Boero, Dora Ramazzotti -- Paratransit in Sub-Saharan African cities: improving and integrating informal services / Eric Bruun, Roger Behrens -- UK DRT: from niche market to total transport? / Barry Connor -- Community transport in Australia / David Denmark, Nick Stevens -- Demand responsive transport and citizen experiences: insights from rural Norway / Merethe Leiren, Kaare Skollerud -- The roles of 'conventional' and demand-responsive bus services / Peter White -- Technology changing market feasibility / Roger Teal -- An innovative concept for paratransit: flexible mobility on demand / Bilge Atasoy, Takuro Ikeda, Moshe Ben-Akiva -- Transportation network companies and paratransit: issues and opportunities / David Koffman -- The future of paratransit and DRT: introducing cars on demand / Jennifer Kent, Robyn Dowling.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Transportation -- Public Transportation; Road traffic law, motoring offences; Paratransit services